Entrepreneurial knowledge and entrepreneurial intention among accounting students of Technical Universities in Ghana- the role of personal attitude - Padi, Abigail; Musah, Alhassan (Lembaga Penerbit Fakultas Ekonomi dan Bisns, Universitas Trisakti, 2025)
This study aims to explain the mechanism through which employees' attitudes toward corporate social responsibility (CSR) in social enterprises influence organizational citizenship behaviors (OCBs), with job involvement considered as a mediating factor. Based on a sample of 532 employees from Tunisian mutual insurance companies, structural equation modeling confirms the direct positive links between perceived CSR and OCBs. Indirect effects through job involvement reveal that CSR fosters OCBs oriented toward the organization (civic virtue and team spirit), but not those directed toward individuals (mutual help). While existing literature supports the link between CSR and OCBs, few studies have examined the mediating processes involved. This study addresses this gap by demonstrating how CSR perceptions can enhance job involvement, which in turn promotes specific forms of organizational citizenship behaviors. Its findings offer practical implications for managers seeking to leverage CSR to enhance employee engagement, foster citizenship behaviors, and promote sustainable performance.